(untitled) (Journal of Medicine, 2024)
Leishmaniasis, caused by Leishmania spp. and transmitted by infected female phlebotomine sandflies, manifests in various forms. These include visceral, cutaneous, and post-kala-azar dermal leishmaniasis (PKDL). The World Health Organisation (WHO) has officially validated Bangladesh as the first country to eliminate visceral leishmaniasis. However, sustaining this achievement is challenging if PKDL cases remain unchecked because PKDL patients act as human reservoirs. Here, we depict a case of PKDL with mixed skin lesions involving the face and multiple body parts. We hope this will raise a concern among us to be vigilant for such cases and maintain the success of eliminating visceral leishmaniasis. J MEDICINE 2024; 25: 191-192